Applied Linguistic Trends: Use of Audiovisual Resources for English Language Teaching (ELT) in Secondary Classes 11–12 - Singh, Ramesh Bahadur (Southwestern Research Journal, 2024)
The current educational system's primary objective and goal is to enhance the innovative, scientific, and student-centered nature of the teaching-learning process. A wide variety of strategies are employed in the teaching-learning process. These days, more and more people are turning to audiovisual tools, which combine visuals with spoken word to help students learn. Several studies have shown that employing audiovisual tools to educate improves recollection. One of the smartest and most significant stages in educating pupils of various levels and domains is to choose suitable educational medium. Several types of audiovisual aids are used, including overhead projectors (OHP), power point presentations (PPT), white or black board teaching, and flip charts. These medium offers both advantages and disadvantages. There are certain strategies for making them more effective. Audiovisual aids assist in the consolidation of long-term memory of previously taught material. Incorporating a variety of media into lessons at the same time may have numerous positive effects on students.